Energy and CO2 Emissions in German and Colombian Manufacturing Industries: An Econometric Application (2013)
This chapter seeks to determine and analyse the tendencies in carbon dioxide (CO2) emissions for the industries of: Germany that has applied several measures to promote the shift towards a low-carbon economy and Colombia that has shown substantial improvements in the decline of CO2 emissions. This study applies panel data cointegration methods to evaluate the causality between CO2 emissions, production aspects and energy sources. The results indicate that the trend in the countries analysed in this study is to produce more output with less pollution. The trends in CO2 emissions also indicate that there are differences between the developed country and the developing country with respect to emissions levels. Moreover, the results of Germany demonstrate that to achieve economic growth and sustainable development are possible by the reduction of CO2 emissions. For Colombia, the reduction of CO2 emissions requires integral policies that include technical and economic programs and promote the use of new technologies and application of cleaner production.